2008
DOI: 10.1002/pbc.21858
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral primary renal lymphoma with orbital metastasis in a child

Abstract: Primary renal lymphoma (PRL) is a rare condition and bilateral PRL even rarer. Most of these bilateral PRL have been reported in adults. We describe a 3-year-old male with bilateral primary renal B cell lymphoma with orbital metastases. We discuss the difficulties in diagnosis and management of this rare presentation of lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Primary renal NHL generally presents with an abdominal mass, as in the presented case, but renal failure, hematuria, and anemia have also been described [13,14]. Interestingly, Jindal et al [12] recently reported a 3-year-old male with bilateral primary renal B-cell lymphoma that presented with orbital metastases, and was characterized by difficulty in diagnosis and management similar to that in the presented patient. The overall prognosis in patients with bilateral primary renal NHL is poor, especially in those that present with renal failure.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Primary renal NHL generally presents with an abdominal mass, as in the presented case, but renal failure, hematuria, and anemia have also been described [13,14]. Interestingly, Jindal et al [12] recently reported a 3-year-old male with bilateral primary renal B-cell lymphoma that presented with orbital metastases, and was characterized by difficulty in diagnosis and management similar to that in the presented patient. The overall prognosis in patients with bilateral primary renal NHL is poor, especially in those that present with renal failure.…”
Section: Discussionmentioning
confidence: 61%
“…Renal insufficiency associated with tumor lysis syndrome is a frequent complication that clinicians must be aware of [6,7,8]. Bilateral primary renal NHL is an extremely rare condition in the pediatric age group and only a few cases have been reported in the English-language medical literature [9,10,11,12]. Primary renal NHL generally presents with an abdominal mass, as in the presented case, but renal failure, hematuria, and anemia have also been described [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the low incidence of PRNHL, randomized controlled trials (RCT) have not been developed to evaluate the best treatment option, 60 however overall the therapeutic regimen for PRNHL depends on the type of lymphoma (according to the tissue diagnosis and immunohistochemistry results) which is most commonly B cell (diffuse large B cell type). 2 …”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, 83 cases of primary NHL of the kidney have been reported in the English literature so far. 3 69 Herein we will review all the primary renal NHL (PRNHL) reported in the English literature and will report all the clinicopathologic findings in the published cases.…”
Section: Introductionmentioning
confidence: 99%
“…We thoroughly reviewed all 54 cases of PRL reported in the literature since 2002 (Table 1). 4,749 DLBCL was found to be the most common pathological type, and more male than female patients (64.8%) were reported. Additionally, PRL was generally located in the bilateral kidneys in younger patients (<30 years old) and in a unilateral kidney in older patients, indicating that the site of PRL is age-related.…”
Section: Discussionmentioning
confidence: 99%